Motivating and Demotivating Factors for Students With Low Emotional Intelligence to Participate in Speaking Activities (2017)
The study aims to understand what factors may motivate and demotivate students with low emotional intelligence to participate in speaking activities during English class. Participants wrote an emotions journal to identify factors affecting student participation and were then interviewed at the end of the study period in order to elaborate on their experiences. Results showed that male participants experienced a wide range of negative emotions while females experienced a reduced number. However, in comparison, women experienced negative emotions frequently while men experienced them occasionally. Results also showed that males and females differed in the way that they perceived and faced situations, and in how they regulated the emotions generated by these situations.